A representation for convex bodies - Aramyan, Rafik (Armenian Journal of Mathematics, 2013)
In this paper we extend the representation for the support function of centrally symmetric convex bodies to arbitrary convex bodies. We discuss some questions on unique determination of convex bodies and consider some classes of convex bodies in terms of support functions.